1992
DOI: 10.1136/pgmj.68.804.817
|View full text |Cite
|
Sign up to set email alerts
|

Patient recovery following cholecystectomy through a 6 cm or 15 cm transverse subcostal incision: a prospective randomized clinical trial

Abstract: Summary:The effect of incision length on patient recovery following cholecystectomy has not been investigated previously. In this study, 30 patients with symptomatic gallstones were randomized to cholecystectomy through a 6 cm or 15 cm transverse subcostal incision. Postoperative hospital stay was significantly shorter in the 6 cm incision group (median 3 days vs 5 days; P = 0.0069 Mann-Whitney U-test). In the 6 cm group analgesic requirements were reduced (median 2.5 vs 4.5 intramuscular opiate injections per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 7 publications
3
24
0
1
Order By: Relevance
“…Instead of open conventional cholecystectomy "minicholecystectomy" may be used (12,20) and there are papers indicating that hospital stay was shorter after minicholecystectomy, whereas operating times did not differ from those of open conventional cholecystectomy (1,2,35). In only one investigation was there no signi cant intergroup difference in hospital stay, which was extremely high values (11 days) in both groups (41).…”
Section: Discussionmentioning
confidence: 84%
“…Instead of open conventional cholecystectomy "minicholecystectomy" may be used (12,20) and there are papers indicating that hospital stay was shorter after minicholecystectomy, whereas operating times did not differ from those of open conventional cholecystectomy (1,2,35). In only one investigation was there no signi cant intergroup difference in hospital stay, which was extremely high values (11 days) in both groups (41).…”
Section: Discussionmentioning
confidence: 84%
“…It is also possible that a transverse incision may permit a more anatomical dissection of the right colonic flexure. The lengths of the two types of incision were equal, length being another factor with implications for pain [13]. Depending on need, the transverse incision may pass through one or both anterior rectus muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Under these circumstances, the high percentage of open cholecystectomy among our non-randomised patients is not surprising. Nevertheless, the number of conventional open cholecystectomy compared to mini-laparotomy cholecystectomy is a matter of concern, as randomised controlled trials [11-13] have concluded that the surgical trauma is greater after conventional open cholecystectomy than after mini-laparotomy cholecystectomy.…”
Section: Discussionmentioning
confidence: 99%